A framework of the safety culture for the Malaysian construction organisations / Faridah Ismail. - Ismail, Faridah (2009)
The introduction of self-regulation through the enactment of OSHA, 1994 aimed at to promote safety culture. However there is no universally accepted framework has yet been established to enable the profession to quantify and analyze safety culture in the Malaysian construction industry. A prerequisite for self-regulation is to treat safety as an important and integral constituent of daily work routine, rather than as an appendage. The objectives of this research is to identify the factors' characteristics of safety culture; to identify the relationship between the identified factors' characteristics; to identify the safety culture of the construction organisations; to identify the factors' characteristics those significantly influence the safety performance of the construction organisations and to develop a framework to promote safety culture in construction organisations. The sample for the study was selected from the total population of Grade 7 registered contractors obtained from the most current Construction Industry Development Board (CIDB) Directory of Contactors 2003-2004. However, the sample was limited to those building contractors in the area of Klang Valley. The Preliminary Survey, identified leadership, organisational commitment, management commitment, safety training and resource allocation as the practices that embed safety culture into the organisational culture. The factors identified which are behavioural in nature were expanded further to include the aspects of psychological and situational factors formulated into the Main Survey. The Main Survey reveals that the factors' characteristics for safety culture comprised the psychological, the behavioural and the situational factors' characteristics, there is a strong relationship between psychological and behavioural constructs, psychological and situational constructs and between situational and behavioural construct. Further, a high emphasis on psychological, a fairly emphasis on the behavioural factors', a fairly weak internal environment of the organisations were discovered and the external factors shows to have a weak influence on the contractors' safety culture. The results of the chi-squared test showed that there is no significant relationship between level of safety performance and level of psychological; level of behavioural and level of environment. Semi-structured interviews which are qualitative in nature were then conducted among eleven (11) contractors' companies to provide new insights on how the communications founded on mutual trust, shared perceptions between the Senior Management, Safety Officer and Site Supervisor within the organisations. The development of a framework of safety culture for the Malaysian construction companies were feasibily validated by panels represented from the Public Works Department (PWD), Master Builders Association Malaysia (MBAM), KLIA Training and Research Consultant, NIOSH, DOSH and Academician in a local university acknowledged on the appropriateness, the ease of use, and the coverage of the framework.